Mechanical behaviour of cross-country ski racing poles during double poling - Stöggl, S.; Karlöf, L. (Sports Biomechanics, 2013)
The purpose of this study was to evaluate the behaviour of cross-country ski poles during double poling on a treadmill using three-dimensional kinematics. The results were compared with standard laboratory tests of the pole manufacturers. A total of 18 skiers were analysed at two speeds (85% and 95% of the maximal speed) at grades of 1.5% and 7%. Variables describing cycle characteristics, bending stiffness, bending behaviour, and trajectories of the pole markers were analysed. Triangular-shaped poles demonstrated the greatest stiffness and lowest variability in maximal bending. Softer poles demonstrated greater variability in bending behaviour and lost ground contact at high skiing speeds, which for some skiers resulted in failure to complete high-speed tests. Considerable variations in pole behaviour for similar poles between skiers were observed, which might be attributed to differences in technique, indicating that mechanical properties of the poles did not exclusively determine pole behaviour in the dynamic situation. The greatest magnitude of pole bending was in the middle part of the pole, which differed from the standard static pole analysis of the manufacturer. Increases in grade demonstrated the greatest effect on pole bending. Distinct differences from the pole manufacturers' laboratory measures were apparent, suggesting that basic pole testing might be adapted.